A feed-forward relay integrates the regulatory activities of Bicoid and Orthodenticle via sequential binding to suboptimal sites - Datta, Rhea R. (Genes Dev, 2018)
The K50 (lysine at amino acid position 50) homeodomain (HD) protein Orthodenticle (Otd) is critical for anterior patterning and brain and eye development in most metazoans. In Drosophila melanogaster, another K50HD protein, Bicoid (Bcd), has evolved to replace Otd's ancestral function in embryo patterning. Bcd is distributed as a long-range maternal gradient and activates transcription of a large number of target genes, including otd. Otd and Bcd bind similar DNA sequences in vitro, but how their transcriptional activities are integrated to pattern anterior regions of the embryo is unknown. Here we define three major classes of enhancers that are differentially sensitive to binding and transcriptional activation by Bcd and Otd. Class 1 enhancers are initially activated by Bcd, and activation is transferred to Otd via a feed-forward relay (FFR) that involves sequential binding of the two proteins to the same DNA motif. Class 2 enhancers are activated by Bcd and maintained by an Otd-independent mechanism. Class 3 enhancers are never bound by Bcd, but Otd binds and activates them in a second wave of zygotic transcription. The specific activities of enhancers in each class are mediated by DNA motif variants preferentially bound by Bcd or Otd and the presence or absence of sites for cofactors that interact with these proteins. Our results define specific patterning roles for Bcd and Otd and provide mechanisms for coordinating the precise timing of gene expression patterns during embryonic development.